Tan Khoen Swie: A Modernist and Developer of Javanese Cultural Literacy - Rokhim, Mukhammad Nur (Centre for Literary and Cultural Studies, 2025)
Ethical politics in the Dutch East Indies (Indonesia during the colonial period), since 1901, has also been the path to developing literacy and education in colonial Indonesia. The various groups supported education development, including the Theosophy group with a mission to strengthen Eastern culture. On the other hand, the development of education also gave birth to many private printing houses that published literary readings for students. During this period, Tan Khoen Swie played a dual role: entrepreneur, supporter of education, and observer of Javanese spirituality and culture. This 340-page book by Wisnu provides a detailed projection of the figure of Tan Khoen Swie and his thoughts, company, and dedication to publishing educational texts during the national movement to the Old Order.